Hubungan Tingkat Pengetahuan tentang Makanan Kariogenik dan Karies Gigi Tetap Siswa Kelas III di SD Muhammadiyah 2 Denpasar Tahun 2025 - Sirat, Ni Made; Senjaya, Asep Arifin; Supariani, Ni Nyoman Dewi; Agung, Anak Agung Gede; Pradnyaswari, Putu Intan (Jurnal Kesehatan Gigi (Dental Health Journal), 2025)
World Health Organization in 2016, of 100% of school-aged children, 60%-90% experience dental caries. The aim of this research is to determine the relationship between the level of knowledge about cariogenic foods and the caries condition of permanent teeth in class III students at SD Muhammadiyah 2 Denpasar in 2025. This type of research is observational. The type of data used in this research is primary and secondary data using question sheets and direct examination. The results of this research on 50 class III students showed that the majority of students' knowledge level regarding cariogenic foods was in the good category, namely 48 students (96%). Only one student (2%) had sufficient knowledge and one student (2%) had insufficient knowledge. The average knowledge obtained was 92.8. The percentage of permanent dental caries with very low criteria was 42 students (84%), six students (12%) had low caries levels, and two students (4%) had moderate caries levels. The average number of dental caries experienced by students was 0.64, which is included in the very low category. The results of Spearman's correlation analysis obtained a significance value of 0.203, greater than 0.05, meaning there is no relationship between the level of knowledge about carcinogenic foods and permanent dental caries in class III students at SD Muhammadiyah 2 Denpasar in 2025. The conclusion of this research is that students who have knowledge about cariogenic foods with good criteria tend to have low dental caries conditions.